Environmental Education in the Teaching and Learning Process in the Context of Enhancing the Educative Learning Function - Meretukova, Z K; Chinazirova, A R; Blyagoz, N S; Kuprina, N K; Dzhabatyrova, B K (KnE Social Sciences, 2019)
The article substantiates the relevance of the problem of environmental education and discusses various approaches to its solution. The author’s definition of the concepts ”ecology” and ”environmental education” is proposed. The necessity of the syncreticism of environmental and moral-spiritual education is substantiated. Means, methods, pedagogical conditions and stages of environmental education in the teaching and learning process are proposed in the context of enhancing the educative learning function. Keywords: ecological crisis; ecological education; syncretism of environmental and moral education; emotional value attitude; pedagogical conditions.